1990
DOI: 10.1007/bf00318670
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional organization of a transcellular tubulocisternal endoplasmic reticulum in epithelial cells of Reissner's membrane in the guinea-pig

Abstract: The ultrastructure of the epithelial cells of Reissner's membrane (membrana vestibularis) in the guinea-pig is described following vascular perfusion with glutaraldehyde of live, anaesthetised and artificially respirated animals. Postfixation in a solution containing OsO4 and potassium ferricyanide revealed a well-developed tubulocisternal endoplasmic reticulum, not previously described, the continuity of which has been mapped by serial sectioning and reconstruction. Large disc-shaped subsurface cisternae lini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…This relationship prompts the consideration that vesicles budding from the Golgi cisternae fuse to generate the tubular reticulum. Although a connection between the Golgi apparatus and genesis of tubular reticulum has not been entertained previously, retrospective viewing of micrographs of sweat gland clear cells (Baron et al, 1984) and Reissner's membrane cells (Qvortrup and Rostgaard, 1990) reveals close proximity of Golgi complexes to tubulocisternal reticulum in these as in Deiters cells. An attractive aspect of this hypothesis, aside from its relevance to genesis of the reticulum, pertains to its potential for explaining the enigmatic occurrence of abundant, rather characteristic Golgi complexes in cells, like Deiters cells and sweat gland clear cells, that are not generating secretory granules or lysosomes.…”
Section: ) and Perhaps Bear Some Relationship To A Glial Type Of mentioning
confidence: 99%
See 1 more Smart Citation
“…This relationship prompts the consideration that vesicles budding from the Golgi cisternae fuse to generate the tubular reticulum. Although a connection between the Golgi apparatus and genesis of tubular reticulum has not been entertained previously, retrospective viewing of micrographs of sweat gland clear cells (Baron et al, 1984) and Reissner's membrane cells (Qvortrup and Rostgaard, 1990) reveals close proximity of Golgi complexes to tubulocisternal reticulum in these as in Deiters cells. An attractive aspect of this hypothesis, aside from its relevance to genesis of the reticulum, pertains to its potential for explaining the enigmatic occurrence of abundant, rather characteristic Golgi complexes in cells, like Deiters cells and sweat gland clear cells, that are not generating secretory granules or lysosomes.…”
Section: ) and Perhaps Bear Some Relationship To A Glial Type Of mentioning
confidence: 99%
“…This tubular reticulum has been implicated in transcellular ion transport also in Reissner's epithelium (Qvortrup and Rostgaard, 1990) and in transport of K + upgrade across the marginal cells of the stria vascularis (Forge, 1982). Lying close to apical plasmalemma, the tubular reticulum in Deiters cells appears situated to facilitate K' resorption from Nuels space and serve as an ion reservoir or mediate ion diffusion down a gradient toward scala tympani.…”
Section: ) and Perhaps Bear Some Relationship To A Glial Type Of mentioning
confidence: 99%
“…Cells enriched in this organelle specialize to a large extent in the transepithelial movement of fluid and ions. Sites known to express TCER include epithelium of the intestine (Møllgå rd and Rostgaard, 1981), human eccrine sweat gland (Baron et al, 1984), liver (Møller et al, 1983), proximal renal tubule, gall bladder, and choroid plexus (Møllgå rd and Rostgaard, 1978Rostgaard, , 1981Rostgaard and Møller, 1980;Bergeron and Thiéry, 1981) as well as Reissner's membrane (Qvortrup and Rostgaard, 1990) and the stria vascularis (Forge, 1982) in the cochlea.…”
mentioning
confidence: 99%
“…Although it has been shown that strial marginal cells and Reissner's membrane epithelial cells express TCER (Forge, 1982;Qvortrup and Rostgaard, 1990), whether other cochlear cells functioning in ion transport are endowed with CR is not known. The present inquiry addressed this question by examining outer hair cells (OHCs) as part of a general survey of the cochlea for the organelle.…”
mentioning
confidence: 99%
“…, 1978Rostgaard and Møllgård, 1980;Bergeron and Thiéry, 1981), and human eccrine sweat gland (Baron et al, 1984). In the cochlea, strial marginal cells (Forge, 1982) and Reissner's epithelium (Qvortrup and Rostgaard, 1990) contain TCER. The CR shown in cochlear fibrocytes and sulcus cells resembles TCER and presumably functions similarly in mediating ion and fluid movement.…”
Section: Discussionmentioning
confidence: 99%